2021
DOI: 10.1158/1078-0432.ccr-21-0625
|View full text |Cite
|
Sign up to set email alerts
|

Circulating HPV DNA as a Marker for Early Detection of Relapse in Patients with Cervical Cancer

Abstract: Financial support: European Union's Seventh Program for research, technological development and demonstration (agreement N°304810), the Fondation ARC pour la recherche contre le cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…Screening with Pap and/or HPV tests remains the best strategy for cervical cancer screening. Although the value of HPV ctDNA in diagnosing cervical premalignant lesions is limited, we believe that this biomarker might nonetheless have the potential to be applied in disease monitoring following the diagnosis of cancer, as shown elsewhere ( 32 , 35 , 36 ). However, the retrospective design of our study did not include the collection of samples at different time points and, therefore, does not allow the evaluation of this biomarker in disease monitoring.…”
Section: Discussionmentioning
confidence: 67%
“…Screening with Pap and/or HPV tests remains the best strategy for cervical cancer screening. Although the value of HPV ctDNA in diagnosing cervical premalignant lesions is limited, we believe that this biomarker might nonetheless have the potential to be applied in disease monitoring following the diagnosis of cancer, as shown elsewhere ( 32 , 35 , 36 ). However, the retrospective design of our study did not include the collection of samples at different time points and, therefore, does not allow the evaluation of this biomarker in disease monitoring.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, ddPCR platforms are likely to have an increasing role in service laboratories to support precision testing in solid and liquid biopsies including for the measurement of circulating HPV and tumour DNA. [52][53][54] There are limitations to the study--although the sample set was well annotated it was still relatively small. A larger study would have conferred greater power to investigate the impact of viral load, particularly in view of the various adjustments.…”
Section: Viral Load and Impact On Clinical Outcomesmentioning
confidence: 99%
“…In the field of cervical cancer, a trial conducted by Jeannot et al showed that the complete clearance of HPV ctDNA observed by the end of treatment of chemoradiation was significantly associated with a longer DFS and could be used as a reliable marker to predict the risk of relapse [ 41 ]. Unfortunately, in this trial we did not study the HPV ctDNA; further studies will be needed to assess the impact of HPV ctDNA in early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%